Factors associated with sleep disorders among adolescent students in rural areas of China - Li, Dan-Lin; Nie, Xin-Yi; Li, Jun; Tao, Yi-Jin; Zhao, Chun-Hua; Zhong, Hua; Pan, Chen-Wei (Frontiers in Public Health, 2023)
Background: This study aimed to determine sleep patterns and the prevalence and association factors of sleep disorders in a regionally representative sample in Mo Jiang, China. Methods: A total of 2346 (participation rate 93.5%) Grade 7 students (aged 13–14 years), including 1213 (51.7%) boys and 1133 (48.3%) girls, participated in the study. All the participants were invited to complete questionnaires that acquired information on sleep patterns, academic performance, academic stress and sociodemographic factors. Sleep disorders were assessed using the Chinese version of the Children’s Sleep Habits Questionnaire. Logistic regression models were also used to explore the associations of sleep disorders with risk factors. Results: Based on the study results, the prevalence rate of sleep disorders among rural adolescents was 76.4%, which is higher than that among urban adolescents. Compared with previous ﬁndings in urban areas, our results indicate that sleep loss is much more severe in rural adolescents. Sleep disorders were positively associated with factors, such as watching TV, academic performance and academic stress (P < 0.05). In addition, girls were more likely to suffer from sleep disorders than boys (P < 0.05). Conclusions: Insufficient sleep and sleep disorders have become common health problems in rural Chinese adolescents.